2011
DOI: 10.5209/rev_laza.2011.v32.37253
|View full text |Cite
|
Sign up to set email alerts
|

Vegetación serial de la cuenca del Río Tinto (Huelva, España): pastos, prados y comunidades rupícolas

Abstract: Resumen: Rufo Nieto, L. & Fuente, V. de la. Vegetación herbácea vivaz de la cuenca del Río Tinto (Huelva, España). Lazaroa 32: 73-89 (2011).Se presentan los resultados del estudio fitosociológico de la vegetación herbácea vivaz de la cuenca del río Tinto. Se reconocen en este estudio 14 comunidades pertenecientes a las clases Isoeto-Nanojuncetea (Loto hispidi-Chaetopogonetum fasciculati), Phragmito-Magnocaricetea (Typho angustifoliae-Phragmitetum australis, Glycerio declinatae-Eleocharitetum palustris, Glyceri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…S3 ). Whether these populations would disappear, the dominant phytosociological associations ( Carici reuterianae - Betulum celtiberica , Rodríguez-Guitián et al, 2017 and Caricetum tartessianae , Molina, 1996 ; Navarro, Molina & Moreno, 2001 ; Rufo Nieto & De la Fuente García, 2011 ) that forms part of the Iberian riparian forests will be affected. Carex reuteriana subsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S3 ). Whether these populations would disappear, the dominant phytosociological associations ( Carici reuterianae - Betulum celtiberica , Rodríguez-Guitián et al, 2017 and Caricetum tartessianae , Molina, 1996 ; Navarro, Molina & Moreno, 2001 ; Rufo Nieto & De la Fuente García, 2011 ) that forms part of the Iberian riparian forests will be affected. Carex reuteriana subsp.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to its conservation status, it has been listed under different conservation categories according to a variety of regional and global red lists ( Bilz et al, 2011 ; Domina, 2011 ; Rossi et al, 2013 ; Urbani, Calvia & Pisanu, 2013 ). Both species are conspicuous, tussock-forming plants, which are ecologically relevant as they are dominant and characteristic taxa in the plant communities where they live (phytosociological ranks: association, alliance, class; Molina, 1996 ; Navarro, Molina & Moreno, 2001 ; Rufo Nieto & De la Fuente García, 2011 ; Gianguzzi et al, 2013 ; Rodríguez-Guitián et al, 2017 ). Previous studies revealed a strong genetic structure in both species driven by geography, with distinct genetic clusters corresponding to disjunct populations ( Jiménez-Mejías et al, 2011 ; Benítez-Benítez et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%